Health condition dynamics in fire-damaged pine stands of the Kharkiv City green belt - Voron, V. P.; Melnyk, Ye. Ye.; Sydorenko , S. H. (Forestry and Forest Melioration, 2021)
Introduction Wildfires in Kharkiv green zone are among the greatest dangers both in terms of risks to life and health of the population, industrial and infrastructural resources, and from the ecological point of view due to forest ecosystem damage. The large population in the metropolis seriously increases the risk of forest fires, which threatens the existence of forests in this area. Due to this, the study of the changes in the health condition of damaged stands will give the possibility to develop predictions and scenarios for damaged forests and forestry treatments to stabilize them. The aim of the study was to assess the long-term dynamics of the health condition of pine stands in Kharkiv green belt, damaged by surface fires. Materials and Methods The study is based on data obtained during long-term monitoring of damaged pine stands. Sample plots were established during 2007–2011 in the pine stands within Vasyshchevo Forestry in Zhovneve State Forest Enterprise. The health condition of the trees in the stands was assessed in the year of fire damage, and annually for 13 years period. Taxonomic and morphological characteristics such as tree height, diameter, and Kraft class of trees were determined. The intensity of damage to stands was assessed by the level of defoliation (loss of needles, %) and discoloration of tree crowns (%). The health condition index (Ic) was calculated as a weighted average of different categories of health condition of each tree in the stand (from I to VI). Results The tendencies of fires for 2002–2021 in Kharkiv green belt and their localization at separate forest units, as well as forest site conditions and pine stands characteristics have been analysed. We have compared long-term studies (up to 13 years) of changes in the health condition of damaged pine stands after surface fires of different intensities, taking into account the season of the year. When selecting sample plots for the study, we considered changes in the condition and number of trees as a result of post-fire and natural tree mortality. The present study determined the influence of such factors as anthropogenic impact, sanitation felling, repeated fires, insect pests, and phytopathogens on tree mortality. These data were used to identify changes in pine stands after surface fires of different intensity and seasons of occurrence, as well as to predict further growth and development of such stands. Conclusions In the green belt, forest units with the highest risks of fires have been identified. Such areas require additional fire prevention treatments and fuel management approaches. During the 13-year period after the fire, the stands damaged by summer fires recovered longer, and the number of dead trees was 2–3 times higher than in the stands damaged by spring fires. A noticeable difference between summer and spring fires is the appearance of weakened and dead trees even after a considerable period of time, 5–13 years after fire damage, in the case of spring fires. The negative impact of surface fires that had low (the scorch height is up to 0.5 m) and medium (the scorch height is 0.5–1.5 m) intensity is manifested primarily in the weakening of pines in the year of fire damage. In the following years, a significant regeneration of tree crowns was registered. After high-intensity summer surface fires (the scorch height is above 1.5 m), a significant part of trees died in the first year after the damage. In such areas, the health of pine trees did not fully recover even 13 years after the fire: the vast majority of trees were severely weakened and had a high risk of mortality.